Penentuan Siswa SMK Kimia Analisa Terbaik Yang Akan Dikirim Mengikuti Olimpiade Kimia Tingkat Nasional Menerapkan Metode Entropy dan MOORA - Yendrizal, Yendrizal (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
SMK Chemistry Analysis is a special and concentrated junior high school in matters related to chemistry, chemistry is very important in human life because every element on earth contains chemicals so chemistry is a department that is very much in demand by many circles, both industrial and non-industrial, so that many students, especially those majoring in Chemistry Analysis, want to do their best to prove their ability in the lessons they persevere by taking part in the Olympics, the Olympics that are followed are usually at the national level between SMK / SMA students and the equivalent which will later become an honor If you can win the chemistry Olympiad, to win an Olympiad it takes students who are really able to take part in competitions, of course schools need to make a selection first in order to get students who really excel and deserve to take part in the Olympics, in the selection it must be done. Do it systematically in order to produce fairness in student selection and minimize failures in participating in the national level chemistry Olympiad, namely by using a decision support system by applying the MOORA method which previously used the entropy method in obtaining subjective weights that will be used in calculating all aspects of decision support